This England : Essays on the English nation and Commonwealth in the sixteenth century - Collinson, Patrick (Book collections on Project MUSE., 2011)
This England is a celebration of 'Englishness' in the sixteenth century, and examines the growing conviction of 'Englishness' through the rapidly developing English language; the reinforcement of cultural nationalism as a result of the Protestant Reformation; the national and international situation of England at a time of acute national catastrophe; and of Queen Elizabeth I, the last of her line, who remained unmarried throughout her reign, refusing to even discuss the succession to her throne. In a series of essays, Collinson explores the conviction among leading Elizabethans that they were.